Exploring a web-based interactive writing assessment WISSE: User experiences - Degeng, Putu Dian Danayanti; Hamamah, Hamamah; Emaliana, Ive; Hapsari, Yulia; Fadillah, Alifa Camilia (Universitas Islam Negeri Banda Aceh, 2024)
This paper aims to investigate the user experiences of Web-based Integrated Writing Assessment (WISSE) developed to help lecturers and learners provide and navigate feedback for academic writing in English. User experience is one of the crucial elements for product success and reception in Research and Development (R & D). Aspects of user experience highlighted in this study are web features, ease of use, and design. The participants involved were two lecturers and twenty-eight learners from the English Language Education and the English Literature study program at one of the prominent universities in Malang. At first, both learners and lecturers created a temporary account on the web prototype, and they were assigned two different roles: learners wrote and submitted a short argumentative essay on the application, and lecturers provided feedback on the essays through a personal comment box. At the end of the trial, both groups revealed their experience and inputs on the features, operation accessibility, and web design through questionnaires. To a large extent, both lecturers and learners were satisfied with the goal of the application to provide easy accessibility to assessing academic text. However, both groups agreed that more distinctive features should be added, along with a manual book and language switch feature, as it is attainable that the future users of WISSE will not be limited to EFL learners. The user trial results illustrate that while WISSE needs further development and revision, it exhibits proper performance and is prepared for large-scale use.